Expression, characterization and organic solvent stability of protease from Bacillus pumilus 115b - Nazarirad, Peiman (2012)
Organic solvent stable proteases have potential to be used in non‐aqueous enzymatic reactions. Therefore, organic solvent stability study of these enzymes could contribute to a better understanding of their functions. Bacillus pumilus 115b produce organic solvent stable protease. The protease showed stability in 25% (v/v) benzene and toluene and it was activated by non‐polar organic solvents. Protein engineering is useful to clarify the mechanisms by which the enzymes are stable in the presence of organic solvents. In the current study the organic solvent stable protease gene (1065 bp) from Bacillus pumilus 115b was cloned and expressed in E.coli BL21 (DE3). To achieve the maximum production of recombinant protease, parameters such as temperature, inducer concentration (IPTG), induction time and OD600nm were optimized. The optimum conditions assessment consisting of; cultivation temperature at 25°C, induction timing at late stage (OD600nm, 0.75) of exponential growth, IPTG 0.8 mM and post induction time for 8 h were determined. The recombinant organic solvent stable protease from Bacillus pumilus 115b (55 kDa) was purified by affinity chromatography using Nickle‐Sepharose. Protein peak was formed from fraction 36‐40. In the range of 375‐400 mM imidazole, the target protein was eluted and purified. The recombinant purified protease was verified using SDS‐PAGE and Western blot analyses. The purification of recombinant organic solvent protease (OSSP) was increased to 126.89 fold with 72.83% recovery. The purified protease was shown to be active between 30 to 60°C with an optimal temperature of 55°C. Thermostability profile indicated that the protease was stable at 37, 45 and 50 °C for 30 min. Further increase in temperature above 60 °C resulted in a reduction of the activity. The pH activity of the purified protease was 7 to 10 with an optimum pH of 9.Low protease activity was detected at pH below 6.0. Moreover less than 50 % of maximal protease activity was detected at pH above 10.0. The result showed that, the activity retained 68.3, 38.3 and 10 % of maximal activity at pH 10, 11 and 12, respectively. No activity was detected at pH 4 and very low protease activity was observed at pH 5. pH stability study showed that recombinant protease was fairly stable at alkaline pH condition. The enzyme was stable between pH 7.0 to 11. Further increment in pH value (12) caused 58.07 % loss of the maximal activity. Meanwhile 45.16% of maximal activity was retained in pH 6; treatment of the enzyme at pH below 5 almost destabilized the protease activity. Metal ion study revealed that Ca++ ion increased the activity of purified recombinant protease to 118.18% compared to control while Sr++ and Na++ gave negligible enhancement effects on the activity of protease. Whereas, variable inhibitory effects were observed in the presence of Zn++ (77.28%), Mn++ (71.82%), Cu++ (53.64%), K+(45.64%), Fe+++ (45.46) and Co++(32.78%). In regard to inhibitors, phenylmethanesulfonyl fluoride (PMSF) caused 100% inactivation of the protease. The purified protease was inhibited 89.2% by Diisopropylfluorophosphate (DFP). Inhibitory effects were also observed in the presence of ethylenediaminetetraacetic acid (EDTA) and bestatin with 43.4 and 31.67%, respectively. As PMSF completely deactivated the recombinant protease activity, this protease was grouped as serine protease. The casein, a major protein component in milk was the most susceptible to hydrolysis compared to other substrates (albumin, haemoglobin, azocasien and azocoll). It was found that hemoglobin was less suitable substrate compared to casein. Recombinant protease 115b also revealed substrate specificity toward Albumin and azocasien. This protease also showed the ability of hydrolysing large molecules such as azocoll. Organic solvent stability study showed that the recombinant protease was stable in the presence of various organic solvents. It was found that the residual activity reduced to 50, 66 and 79% of the initial when enzyme was exposed to acetonitrle, diethylamine and butanol, correspondingly (log Po/w <2). The residual activity of recombinant purified protease was enhanced against nonpolar organic solvents including n‐dodecane, n‐tetradecane and n‐hexadecane (log Po/w >4) 175, 197 and 219%, respectively. On the other hand, application of solvents having a log P (2 to 4) showed fluctuations of 56 ‐115% in comparison to control. To find the amino acid residue(s) responsible for the organic solvent stability of the protease, random mutation was carried out using error‐prone PCR (EP‐PCR) method. A mutated transformant which retained its protease activity but different in stability (a change in residual activity in acetonitrile) was selected. The mutant (M2‐17) showed decreased stability in the presence of acetonitrile. The mutant protease was also less stable in the presence of various organic solvents compared to recombinant protease. The residual activity of mutant protease decreased in polar solvents. It was found that the residual activity reduced to 18, 27.27 and 34% of initial while enzyme was exposed to acetonitrile, diethylamine and butanol, correspondingly (log Po/w <2). The residual activity of mutant protease was enhanced against nonpolar organic solvents including n‐dodecane, n‐tetradecane and nhexadecane (log Po/w >4) 113.63, 136.36 and 156.8%, respectively. Furthermore, solvents having a log P (2 to 4) showed result in fluctuations between 31.81 ‐ 70.45% compare to control. Study of organic solvent on the stability of mutant protease revealed that polar solvents could destabilize the mutant protease more than the recombinant. Optimization and characterization (except organic solvent stability) of mutant M2‐17 showed almost similar result with recombinant protease. This finding revealed the major role of a polar amino acid (Lysine 244) residue merely affecting in the organic solvent stability of protease from Bacillus pumilus 115b. By comparison of the sequences of mutant and recombinant proteases, it was revealed that a point mutation on the polar amino acid (Lysine 244 to Isoleucine) had occurred which could significantly change the organic solvent stability. This finding revealed the polar amino acid (Lysine 244) residue is responsible for organic solvent stability of protease from Bacillus pumilus 115b.